2017
DOI: 10.1302/2046-3758.65.bjr-2017-0330.r1
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and cost effectiveness of a virtual fracture clinic service

Abstract: ObjectivesTo assess the clinical and cost-effectiveness of a virtual fracture clinic (VFC) model, and supplement the literature regarding this service as recommended by The National Institute for Health and Care Excellence (NICE) and the British Orthopaedic Association (BOA).MethodsThis was a retrospective study including all patients (17 116) referred to fracture clinics in a London District General Hospital from May 2013 to April 2016, using hospital-level data. We used interrupted time series analysis with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 16 publications
(24 reference statements)
1
41
0
Order By: Relevance
“…It has been shown in the literature that the immediate effect of an implemented VFC service is a reduction in the number of ED to fracture clinic referrals by between 15% and 28%. 15 , 17 , 43 Additionally, 55–67% of ED referrals that would have been seen in a traditional fracture clinic, were appropriate to be seen in the VFC. 11 , 21 Anderson et al showed a 65% reduction in face-to-face consultations in a fully implemented VFC service.…”
Section: Clinical Efficiencymentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown in the literature that the immediate effect of an implemented VFC service is a reduction in the number of ED to fracture clinic referrals by between 15% and 28%. 15 , 17 , 43 Additionally, 55–67% of ED referrals that would have been seen in a traditional fracture clinic, were appropriate to be seen in the VFC. 11 , 21 Anderson et al showed a 65% reduction in face-to-face consultations in a fully implemented VFC service.…”
Section: Clinical Efficiencymentioning
confidence: 99%
“…The overall discharge rate after review in the VFC ranges greatly from 33% to 60% 11 , 17 , 19 who did not require any formal fracture clinic appointment or further review. The percentage of patients meeting the BOAST 7 guideline (seen within 72 hours in clinic from the ED), ranges from 46% 17 to 100% 22 in the literature. During the current coronavirus pandemic, timely decision making and intervention are key.…”
Section: Clinical Efficiencymentioning
confidence: 99%
See 3 more Smart Citations